Restricted discontinuous phrase structure grammar and its ramifications - VOGEL, CARL (Elsevier, 1994)
This paper presents a phrase structure grammar called Restricted Discontinuous Phrase Structure Grammars DPSGR designed for representing limited forms of discontinuous constituency crossed branches The formalism has only slightly greater than context free generative capacity yet properly less power than the Mildly Context Sensitive Grammars MCSGs The existence DPSGR suggests that there is not a discrete step between the Context Free Grammars CFGs and the MCSGs as suggested by the Joshi conjecture of the convergence of mildly context sensitive formalisms DPSGR is adequate for the description of certain discontinuity phenomena but it is unable to generate important languages like those that express crossserial dependencies
PUBLISHED
Keywords: Computer Science